+0  
 
0
138
1
avatar

3 lg x= lg10

Guest May 17, 2017
Sort: 

1+0 Answers

 #1
avatar+17693 
0

Assuming that 'lg' means 'log' (either base 10 or base 2):

3 lg( x )  =  lg( x3 )

So, the equation becomes  3 lg( x )  =  lg( 10 )     --->     lg( x3 )  =  lg( 10 )     --->     x3  =  10

                                                                                                                         --->       x  =  cuberoot( 10 )

geno3141  May 17, 2017

15 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details